2007
DOI: 10.1080/17435390701556080
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the potentialin vivoecotoxicity of Double-Walled Carbon Nanotubes (DWNTs) in water, using the amphibianAmbystoma mexicanum

Abstract: Because of their specific properties (mechanical, electrical, etc), carbon nanotubes (CNTs) are being assessed for inclusion in many manufactured products. Due to their massive production and number of potential applications, the impact of CNTs on the environment must be taken into consideration. The present investigation evaluates the ecotoxic potential of CNTs in the amphibian larvae (Ambystoma mexicanum ). Acute toxicity and genotoxicity were analysed after 12 days of exposure in laboratory conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 35 publications
5
16
1
Order By: Relevance
“…Induction of defense mechanisms may divert energy otherwise used for reproduction or development [28]. Confusion of DWNTs with food particles may also have contributed to the adverse effects previously mentioned by lowering the food intake efficiency of T. japonicus, as this was also found in other copepod [11] as well as with similar DWNT samples in the case of amphibians [29,30]. The present results also confirmed that DWNTs were not only ingested by T. japonicus but also observed inside their gut cells.…”
Section: Discussionsupporting
confidence: 78%
“…Induction of defense mechanisms may divert energy otherwise used for reproduction or development [28]. Confusion of DWNTs with food particles may also have contributed to the adverse effects previously mentioned by lowering the food intake efficiency of T. japonicus, as this was also found in other copepod [11] as well as with similar DWNT samples in the case of amphibians [29,30]. The present results also confirmed that DWNTs were not only ingested by T. japonicus but also observed inside their gut cells.…”
Section: Discussionsupporting
confidence: 78%
“…Concerning the absence of genotoxicity in erythrocytes of Xenopus larvae, the present results are in agreement with the previous ones obtained on amphibian larvae in the same conditions of exposure to MWNTs (Mouchet et al 2010) and DWNTs (Mouchet et al 2007(Mouchet et al , 2008. The majority of the time, if acute and chronic toxicities are generally observed after CNTs exposure of different biological models, genotoxicity, especially via micronucleus induction mechanism, is not demonstrated.…”
Section: Fe Mo Alsupporting
confidence: 92%
“…Cheng, Flahaut, and Cheng (2007) observed hatching delay in fish eggs exposed to 120 mg L ¡1 of raw SWNTs and 240 mg L ¡1 of raw DWNTs. Neither mortality nor growth inhibition was observed in urodele amphibian larvae up to 1 g L ¡1 of raw DWNTs (Mouchet et al 2007), whereas mortality was observed at 50 mg L ¡1 and growth inhibition from 10 mg L ¡1 in anuran amphibian larvae exposed to raw DWNTs (Mouchet et al 2008(Mouchet et al , 2011 as well as growth inhibition at 50 mg L ¡1 for raw MWNTs exposure (Mouchet et al 2010). Kahru and Dubourguier (2011) calculated on the basis of 34 median values a L(E)C 50 between 1 and 10 mg L ¡1 for SWNTs and MWNTs (L(E)C 50 derived from 77 individual values.…”
Section: Fe Mo Almentioning
confidence: 89%
“…Daphnia magna was shown to be the species most sensitive to CNTs; the lowest NOEC found for this organism was 13 μg/L –1 by Zhu et al (). The amphibian Ambystoma mexicanum presented an NOEC of 105 μg/L –1 (Mouchet et al ) and was the least sensitive species. The PNEC empirical probability distribution obtained from the PSSD had a mean of 86 μg/L –1 with 25th and 75th quantiles of 32 and 111 μg/L –1 , respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%